2011
DOI: 10.1007/s11858-011-0361-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring US textbooks’ treatment of the estimation of linear measurements

Abstract: Learning to estimate a linear measurement is critical in becoming a successful measurer. Research indicates that the teaching of the estimation of linear measurement is quite open and that instruction does not make explicit to students how to carry out estimation work. Because written curriculum has been identified as one of the main sources affecting teachers' instruction and students' learning, this study examined how estimation of linear measurement tasks were presented to students in three US elementary ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Fourth, also pertaining to measurement estimation, was the extent to which curricula differ with respect to children's use of non-standard units, which research has shown to be a powerful underpinning of conceptual and procedural competence (Anestakis & Desli, 2014;Chang et al, 2011). Here, the Scottish and Welsh curricula see a role for non-standard units, with the Scottish asserting that 'measuring and estimating with non-standard units develops understanding of why standard units are necessary and help to provide an estimation of size' (ES, 2016, p. 166), while the Welsh alludes to the same notion by expecting children to 'make a sensible estimate of measurement in length, height, weight and capacity that can be checked using non-standard measures' (CW, 2015, p. 33).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, also pertaining to measurement estimation, was the extent to which curricula differ with respect to children's use of non-standard units, which research has shown to be a powerful underpinning of conceptual and procedural competence (Anestakis & Desli, 2014;Chang et al, 2011). Here, the Scottish and Welsh curricula see a role for non-standard units, with the Scottish asserting that 'measuring and estimating with non-standard units develops understanding of why standard units are necessary and help to provide an estimation of size' (ES, 2016, p. 166), while the Welsh alludes to the same notion by expecting children to 'make a sensible estimate of measurement in length, height, weight and capacity that can be checked using non-standard measures' (CW, 2015, p. 33).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, with respect to measurement estimation, the only common thread across the three curricula was the use of non-standard units, which research has shown to be a powerful underpinning of later conceptual and procedural competence (Chang et al, 2011). In this respect, the Danish curriculum clearly connected non-standard units to estimation, the Norwegian emphasised the use of non-standard units in general but offered nothing in respect of estimation, while the Swedish had nothing related to non-standard units, with the exception of a single reference in the non-statutory guide to assessment for learning.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative estimation (from here on simply "estimation") involves assigning a cardinal number to a discrete collection of objects or other unknown quantity (e.g., length, area, volume) without the precision of actual counting or using formal measurement tools. Estimation is a best guess or approximation based on the available information and is generally exercised when precise calculations or measurements are not possible or not necessary (Chang et al 2011). Its importance in children's education is twofold: first, the exercise of estimation skills is ubiquitous in everyday life, both in school and out of school, across several domains of everyday life; second, estimation skills support the development of higher level mathematical thinking and reasoning (Andrews et al 2022;Rittle-Johnson et al 2001;Russo et al 2022), correlating with standardized achievement test performance as well as arithmetic and magnitude comparison (Opfer and Siegler 2007).…”
Section: Assessing the Analytical Skill Of Estimationmentioning
confidence: 99%